2021
DOI: 10.3390/molecules26113174
|View full text |Cite
|
Sign up to set email alerts
|

Camu-Camu Fruit Extract Inhibits Oxidative Stress and Inflammatory Responses by Regulating NFAT and Nrf2 Signaling Pathways in High Glucose-Induced Human Keratinocytes

Abstract: Myrciaria dubia (HBK) McVaugh (camu-camu) belongs to the family Myrtaceae. Although camu-camu has received a great deal of attention for its potential pharmacological activities, there is little information on the anti-oxidative stress and anti-inflammatory effects of camu-camu fruit in skin diseases. In the present study, we investigated the preventative effect of 70% ethanol camu-camu fruit extract against high glucose-induced human keratinocytes. High glucose-induced overproduction of reactive oxygen specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 49 publications
0
17
0
1
Order By: Relevance
“…The Nrf2 signaling pathway plays a key role in the antioxidant defense system against oxidative stress. 42 Expression of HO-1 is regulated by Nrf2. Oxidative stress encourages translocation of Nrf2 to the nucleus, where it upregulates the HO-1.…”
Section: Discussionmentioning
confidence: 99%
“…The Nrf2 signaling pathway plays a key role in the antioxidant defense system against oxidative stress. 42 Expression of HO-1 is regulated by Nrf2. Oxidative stress encourages translocation of Nrf2 to the nucleus, where it upregulates the HO-1.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that Nrf2 signaling pathway is the most important pathway against oxidative stress [32]. Hence, we investigated the effect of LJP on Nrf2 and its downstream antioxidases, heme oxygenase-1…”
Section: Effect Of Ljp On Nrf2 Ho-1 and Nqo1 Protein Expression In Sgs After Irradiationmentioning
confidence: 99%
“…It is well known that Nrf2 signaling pathway is the most important pathway against oxidative stress [32]. Hence, we investigated the effect of LJP on Nrf2 and its downstream antioxidases, heme oxygenase-1 (HO-1) and quinone oxidoreductase-1 (NQO1), post radiation using immuno uorescence or immunohistochemistry.…”
Section: Effect Of Ljp On Nrf2 Ho-1 and Nqo1 Protein Expression In Sgs After Irradiationmentioning
confidence: 99%
“…Along with anti-oxidant activities, camu-camu has shown pharmacological effects, including those that are anti-inflammatory, anti-microbial, anti-hypertensive, and anti-obesity [ 15 , 16 , 17 , 18 ]. In a previous study, we reported the anti-inflammatory activities of camu-camu fruit extract by modulating MAPK and NFAT signaling pathways in keratinocytes [ 19 ]. Despite exerting various pharmacological effects, the anti-allergic effect of camu-camu fruit has not been studied.…”
Section: Introductionmentioning
confidence: 99%